A survey of the farming systems of Vertisol areas of the Ethiopian highlands - Asamenew, G.; Beyene, H.; Negatu, W.; Ayele, G. (International Livestock Centre for Africa, 1993)
In 1986, ILCA carried out informal surveys at Dogollo and Inewari in order to understand the farming systems. Such surveys were also conducted by the Institute of Agricultural Research (IAR) at Ginchi in 1986 and by the Alemaya University of Agriculture at Ada/Debre Zeit in 1988/89. This was followed by one-time detailed formal farm surveys at Dogollo, Inewari and Ginchi in 1988/89. This chapter mostly presents the results of these formal surveys. The objectives of the surveys were to understand the existing farming systems in order to develop appropriate Vertisol technologies, to identify production constraints and opportunities for technological interventions, to identify recommendation domain, and to compile baseline data in order to assist in ex-post Vertisol - technology evaluation. Natural resources, farm resources, crop and livestock interaction, feed production and livestock feeding, constraints to production, livestock production constraints and researchable areas are examined.